Kadar Betakaroten Dan Organoleptik Cake Labu KuningDengan Penambahan Ekstrak Kulit Buah Naga MerahSebagai Pewarna Alami - Krisna Ariyani, Pipit; , Dra. Suparti M,Si (2016)
Pumpkin (Cucurbita moschata) is a type of fruit that contains a lot of batacarotene and yet many processed into food products. This study aims to maximize the potential of pumpkins to be processed into pumpkin cake with the addition of red dragon fruit skin extracts as natural dyes. The method used in this study is completely randomized design (CRD) two Factorial. These factors are the percentage of pumpkin flour (10%, 15% and 20%) and the concentration of red dragon fruit skin extracts (40 ml, 50 ml and 60 ml). Analysis of the data used in this study is kruskel-Wallis nonparametric test for levels of betacarotene and qualitative analysis for organoleptic deskrpstif. The results obtained show the percentage of flour pumpkin and red dragon fruit skin extracts affect the levels of betacarotene and organoleptic cake. Levels of betacarotene is the highest in the treatment P3K3 is the percentage of flour pumpkin 20% and the concentration of skin extracts red dragon fruit 60 ml with high levels of betacarotene at 94.216 ppm, while the levels of betacarotene is the lowest in treatment P1K3 is the percentage of flour pumpkin 10% and the concentration of skin extracts red dragon fruit 60 ml with betacarotene levels of 26.2355 ppm. Treatment with a percentage of 10% pumpkin flour and 15% preferred by the panelists while treatment with a percentage of 20% pumpkin flour Is less preferred by the panelists.